2011
DOI: 10.1124/mol.110.070045
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Defensive Mechanism against Acetaminophen Toxicity in the Mouse Lateral Nasal Gland: Role of CYP2A5-Mediated Regulation of Testosterone Homeostasis and Salivary Androgen-Binding Protein Expression

Abstract: To identify novel factors or mechanisms that are important for the resistance of tissues to chemical toxicity, we have determined the mechanisms underlying the previously observed increases in resistance to acetaminophen (APAP) toxicity in the lateral nasal gland (LNG) of the male Cyp2g1-null/Cyp2a5-low mouse. Initial studies established that Cyp2a5-null mice, but not a newly generated strain of Cyp2g1-null mice, were resistant to APAP toxicity in the LNG; therefore, subsequent studies were focused on the Cyp2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…2B ) included the female-biased OBP7, the male-biased MUP4, the male-only ESP1, the male-biased ESP38, and several male-biased secretoglobins (SCGB1B19, SCGB1B3, SCGB2A2—Mammaglobin, SCGB2B3, SCGB2B7). Secretoglobins are found in mammalian secretions and have important roles in the modulation of inflammation and tissue repair ( Jackson et al, 2011 ), are involved in removing toxins ( Zhou et al, 2011 ), and may have roles in chemical communication ( Karn & Laukaitis, 2015 ). Kallikrein 1-related peptidases were also significantly sexual dimorphic (i.e., female-biased KLK1B22, KLK1B1, and KLK1B3), however, this pattern (though significant) was not consistent across all the females tested.…”
Section: Resultsmentioning
confidence: 99%
“…2B ) included the female-biased OBP7, the male-biased MUP4, the male-only ESP1, the male-biased ESP38, and several male-biased secretoglobins (SCGB1B19, SCGB1B3, SCGB2A2—Mammaglobin, SCGB2B3, SCGB2B7). Secretoglobins are found in mammalian secretions and have important roles in the modulation of inflammation and tissue repair ( Jackson et al, 2011 ), are involved in removing toxins ( Zhou et al, 2011 ), and may have roles in chemical communication ( Karn & Laukaitis, 2015 ). Kallikrein 1-related peptidases were also significantly sexual dimorphic (i.e., female-biased KLK1B22, KLK1B1, and KLK1B3), however, this pattern (though significant) was not consistent across all the females tested.…”
Section: Resultsmentioning
confidence: 99%
“…The Cyp2f2-null mouse joins three other mouse models reported to target members of the Cyp2 gene clusters on mouse chromosome 7: the Cyp2g1-null/Cyp2a5-low model (Zhuo et al, 2004), the Cyp2a5-null model , and the Cyp2g1-null mouse model (Zhou et al, 2011). As with Cyp2a5-null and Cyp2g1-null models, the Cyp2f2-null mouse was generated on a B6 genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we analyzed the Harderian gland (the source of heteroglobin that may mediate behavior in hamsters) (Dominguez 1995;Alvarez et al 2002); kidney, which was compromised in a uteroglobin (Ug) knockout (Zhang et al 1997); and liver, a major site of detoxification that might be affected by toxins that could not be bound and removed in an Abp knockout animal (Zhou et al 2011). H&E staining revealed no discernable structural differences across tissues, including submandibular gland (Figure 1), sublingual, lacrimal, parotid, Harderian, liver, kidney, and ovaries (female only) ( Figure S3), harvested from the three genotypes.…”
Section: Histological Assessment Of Tissue Structurementioning
confidence: 99%
“…Another knockout mouse project produced a Cyp2g1-null/ Cyp2a5-low mouse and showed that toxin metabolism in the LNG of the male treated with large amounts of APAP upregulated a27 and bg27 expression (Zhou et al 2011). This apparently quenched reactive APAP metabolites and thereby spared critical cellular proteins from inactivation.…”
Section: Overall Impact Of Knocking Out the Abp Genesmentioning
confidence: 99%
See 1 more Smart Citation